Β-Hydroxybutyrate Ameliorates Aβ-Induced Downregulation of TrkA Expression by Inhibiting HDAC1/3 in SH-SY5Y Cells. (20th January 2020) - Li, Xinhui; Zhan, Zhipeng; Zhang, Jingzhu; Zhou, Fuyuan; An, Li
Tyrosine kinase receptor A (TrkA) plays an important role in the protection of cholinergic neurons in Alzheimer's disease (AD). This study was designed to investigate whether β-hydroxybutyrate (BHB), an endogenous histone deacetylase (HDAC) inhibitor, upregulates the expression of TrkA by affecting histone acetylation in SH-SY5Y cells treated with amyloid β-protein (Aβ). The results showed that BHB ameliorated the reduction of cell vitality and downregulation of TrkA expression induced by Aβ. Furthermore, BHB inhibited the upregulation of HDAC1/2/3 expression and downregulation of histone acetylation (Ace-H3K9 and Ace-H4K12) levels in Aβ-treated cells. The expression of TrkA was upregulated in HDAC1- or 3-silenced SH-SY5Y cells. However, there was no significant difference in TrkA expression between the HDAC2 knockdown and control cells. In conclusion, this study demonstrates that BHB protects against Aβ-induced neurotoxicity in SH-SY5Y cells. The underlying mechanism of the effect may be associated with the upregulation of TrkA expression by inhibiting HDAC1/3.